Statistical design for optimal physical and biomechanical characteristics of biocomposite prostheses - Ibrahim Hassan Kobe; Abdulrahman Asipital Salawu; Abolarin Mathew Sunday; Adedipe Oyewole; Okoro Gregory Uzoma; Peter Olorunleke Omoniyi; Tien-Chien Jen (Scientific African)
The mechanical properties of many prostheses are the causes of the stress shielding effect resulting from the imbalance of the prosthesis and human bone, which leads to the premature failure of the prosthesis after installation for bone replacement or repair. The present study uses statistical design to obtain optimal biomechanical properties of biocomposite prostheses to replace orthopaedic bone. The study utilized Pure Titanium (P-Ti) powder reinforced with Hydroxyapatites (Ha) and Calcium Carbonate (CaCO3) as the factors of the experiment, and the physical and mechanical properties were considered as the response. The experiment design was conducted with statistical software (Design Expert) using Determinant Optimal Mixture Design of Experiment (DM-DOE) and analyzed using analysis of variance (ANOVA). Biocomposites were developed using powder metallurgy techniques, and the experimental samples' mechanical, physical, and morphological characteristics were analyzed. The result showed that the optimum biocomposite formulations are 68.36 Ti, 18.36 Cow Bone-Based Hydroxyapatites (CB-Ha), and 8.17 CaCO3 by maximizing the mechanical properties and minimizing stiffness and physical properties suitable for the replacement bone. The results revealed a closer value of bone modulus with the decreased modulus (54.23 GPa), density (4.09 g/cm3), and porosity (9.56 %). There was also an enhancement of other mechanical properties with predicted compressive strength (162.17 MPa), Hardness (378.62 Hv), impact strength (11.43 KJ/m2), and Fracture toughness (26.11 MPa m0.5). The ANOVA revealed that CB-Ha and CaCO3 are crucial factors in minimizing the prosthesis stiffness, which has interactive effects on the formulation of biocomposite.